Standardization of Epidemiological Surveillance of Invasive Group A Streptococcal Infections . (15th September 2022) - Miller, Kate M; Lamagni, Theresa; Cherian, Thomas; Cannon, Jeffrey W; Parks, Tom; Adegbola, Richard A; Pickering, Janessa; Barnett, Tim; Engel, Mark E; Manning, Laurens; Bowen, Asha C; Carapetis, Jonathan R; et al.
Abstract: Invasive group A streptococcal (Strep A) infections occur when Streptococcus pyogenes, also known as beta-hemolytic group A Streptococcus, invades a normally sterile site in the body. This article provides guidelines for establishing surveillance for invasive Strep A infections. The primary objective of invasive Strep A surveillance is to monitor trends in rates of infection and determine the demographic and clinical characteristics of patients with laboratory-confirmed invasive Strep A infection, the age- and sex-specific incidence in the population of a defined geographic area, trends in risk factors, and the mortality rates and rates of nonfatal sequelae caused by invasive Strep A infections. This article includes clinical descriptions followed by case definitions, based on clinical and laboratory evidence, and case classifications (confirmed or probable, if applicable) for invasive Strep A infections and for 3 Strep A syndromes: streptococcal toxic shock syndrome, necrotizing fasciitis, and pregnancy-associated Strep A infection. Considerations of the type of surveillance are also presented, noting that most people who have invasive Strep A infections will present to hospital and that invasive Strep A is a notifiable disease in some countries. Minimal surveillance necessary for invasive Strep A infection is facility-based, passive surveillance. A resource-intensive but more informative approach is active case finding of laboratory-confirmed Strep A invasive infections among a large (eg, state-wide) and well defined population. Participant eligibility, surveillance population, and additional surveillance components such as the use of International Classification of Disease diagnosis codes, follow-up, period of surveillance, seasonality, and sample size are discussed. Finally, the core data elements to be collected on case report forms are presented.